2021
DOI: 10.3389/fnut.2021.719144
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein From Different Sources Exerted a Great Impact on Lipid Metabolism and Mitochondrial Oxidative Phosphorylation in Rat Liver

Abstract: Associations between meat diets and human health have been widely considered. In this study, we focused on long-term effects of different sources of meat protein on liver metabolic enzymes. For 90 days, rats were fed with semisynthetic diets that differed only with protein source. Casein was used as a reference and isolated soybean, fish, chicken, pork, and beef proteins were compared. Changes in liver proteome were determined by isobaric tag for relative and absolute quantitation (iTRAQ) labeling and liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…An increasing body of research from recent years has shown that the intake, digestion, and absorption of dietary meat protein can significantly affect physiological functions and metabolic changes. [ 11–13,27 ] The results of this study indicate that compared with the XWH0 and XWH1 groups, the body weight gain and epididymal fat weight decreased after XWH2 and XWH3 intake, suggesting that the prolonging of ripening period of Xuanwei ham may affect its nutrient digestibility and fat accumulation. Casein intake has been reported to help prevent weight gain among the protein sources tested, [ 28,29 ] and was consistent with the body weight change in Casein group observed in this study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An increasing body of research from recent years has shown that the intake, digestion, and absorption of dietary meat protein can significantly affect physiological functions and metabolic changes. [ 11–13,27 ] The results of this study indicate that compared with the XWH0 and XWH1 groups, the body weight gain and epididymal fat weight decreased after XWH2 and XWH3 intake, suggesting that the prolonging of ripening period of Xuanwei ham may affect its nutrient digestibility and fat accumulation. Casein intake has been reported to help prevent weight gain among the protein sources tested, [ 28,29 ] and was consistent with the body weight change in Casein group observed in this study.…”
Section: Discussionmentioning
confidence: 83%
“…[7] However, excessive intake of meat and processed meat may increase the risk of metabolic disorders and the intestinal microflora disorders. [8,9] Recent studies have indicated that not only the intake of meat protein from different sources can significantly affect the growth performance, lipid metabolism, oxidative stress, and inflammatory immunity of the body, [10][11][12][13][14] but also the meat proteins by different processing methods can affect the digestion, absorption, and intestinal microbiota of host due to the different amino acid derivatives and oligopeptides metabolites. [15][16][17] Therefore, it is especially important to study the physiological function and nutrient metabolism of dietary meat proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, subsequent study showed that Timm13 highly predicted the overall survival (OS) and relapse-free survival (RFS) of basal breast cancer, and was identified as one of the essential genes for triplenegative breast cancer (TNBC) through transcriptomics. In this mechanism, the targeted knockdown of Timm13 reduced the proliferation potential of the cell proteome and found that in the chicken, pork, beef and fish protein diet groups, the levels of translocase of inner mitochondrial membrane (Timm13, Timm8b and Timm9) were relatively low; thus, the meat protein diet could reduce the energy production level of the liver [44]. Recently, Kim et al found that Timm13 showed reduced expression in human Alzheimer's disease brain tissues [45].…”
Section: Discussionmentioning
confidence: 99%
“…Both the source and amount of dietary protein have been shown to influence metabolic health in previous rodent studies [ 36 , 37 , 38 ]. However, the majority of this work has been conducted in adult (mostly male) animals.…”
Section: Discussionmentioning
confidence: 99%